2009
DOI: 10.1002/pen.21561
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and extrusion foaming of chain‐branched poly(lactic acid)

Abstract: Rheology and extrusion foaming of chain-branched poly(lactic acid)Mihai, Mihaela; Huneault, Michel A.; Favis, Basil D.Contact us / Contactez nous: nparc.cisti@nrc-cnrc.gc.ca. In this study, the effect of macromolecular chainbranching on poly(lactic acid) (PLA) rheology, crystallization, and extrusion foaming was investigated. Two PLA grades, an amorphous and a semi-crystalline one, were branched using a multifunctional styrene-acrylicepoxy copolymer. The branching of PLA and its foaming were achieved in one-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
204
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(219 citation statements)
references
References 49 publications
8
204
2
Order By: Relevance
“…Some experiments have been conducted by our team researchers in previous works [5][6][7][8][9][11][12][13]. We showed that the structural modification of PLA highly increased the shear rheological properties (melt strength, zero-shear viscosity, elasticity, shear-thinning behavior) and contributed to very long relaxation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experiments have been conducted by our team researchers in previous works [5][6][7][8][9][11][12][13]. We showed that the structural modification of PLA highly increased the shear rheological properties (melt strength, zero-shear viscosity, elasticity, shear-thinning behavior) and contributed to very long relaxation process.…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have motivated considerable research efforts. In particular, two strategies are presented here: (i) modification of PLA through branched architecture with chain-extension reactions to compensate for the molecular weight decrease caused by the processing degradation [7,8] and (ii) blending PLA with other natural or synthetic materials such as Polycaprolacton (PCL), starch, poly (butylene adipate-co-terephtalate) (PBAT), poly(butylene succinate-co-adipate) (PBSA), etc. [9].…”
Section: Introductionmentioning
confidence: 99%
“…Najafi et al [21] prepared PLA-clay nanocomposites using polycarbodiimide, tris(nonyl phenyl) phosphate and Joncryl ADR-4368 as chain extenders. Liu et al [16], Corre et al [22], Mihai et al [23] and Pilla et al [24], employed a multi-functional epoxy-based chain extender (Cesa-Extend from Clariant) to give rise to branched structures of PLA. Recently, Han et al [25] used polysilsesquioxane microspheres as novel chain extenders to improve the thermal stability of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are very few studies about extrusion foaming of PLA (Reignier et al, 2007;Mihai et al, 2010). Mihai et al studied the rheology and extrusion foaming of chainbranched PLA at a temperature between 180 o C to 200 o C (Mihai et al, 2010).…”
Section: Rheology Of Pla and Plgamentioning
confidence: 99%
“…Mihai et al studied the rheology and extrusion foaming of chainbranched PLA at a temperature between 180 o C to 200 o C (Mihai et al, 2010). Two PLA grades, an amorphous and a semicrystalline one, were branched using a multifunctional styrene-acrylic-epoxy copolymer.…”
Section: Rheology Of Pla and Plgamentioning
confidence: 99%